Dinamika Teknologi Informasi Dan Pengendalian Internal Terhadap Sistem Informasi Akuntansi - Steiskarani, Khansa Lungit; Sitinjak, Norman Duma (LPPM UBSI Kampus Kota Tegal, 2024)
Abstract This research examines the influence of information technology and internal control on accounting information systems. This research uses a quantitative approach with primary data from questionnaire results. The sample used was 30 people. The research used multiple linear regression analysis and hypothesis testing was carried out using the t test and F test. The results of the research showed that information technology and internal control had an effect on the accounting information system. Speed of access and maintenance of hardware software supports the application of information technology. Appropriate delegation of authority and responsibility as well as good employee understanding of authority and responsibility support internal control.